2006
DOI: 10.1007/s10719-006-9016-x
|View full text |Cite
|
Sign up to set email alerts
|

Single chain human chorionic gonadotropin, hCGαβ: Effects of mutations in the α subunit on structure and bioactivity

Abstract: The strategy of translationally fusing the subunits of heterodimeric proteins into single chain molecules is often used to overcome the mutagenesis-induced defects in subunit interactions. The approach of fusing the alpha and beta subunits of human Chorionic Gonadotropin (hCG) to produce a single chain hormone (phCGalphabeta) was used to investigate roles of critical residues of the alpha subunit in hormone receptor interaction and biological activity. The alpha subunit was mutated using PCR-based site-directe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
1
4
0
1
Order By: Relevance
“…The effect of these substitutions on the in vitro bioactivity was highly correlated with their effects on the receptor binding activity. It was repeatedly demonstrated in media and buffers with various salt concentrations, and confirmed by studies in other laboratories ( 25 , 26 ) as well as by using CHO-TSHR cells with largely depleted pool of the negatively charged cell surface proteoglycans. Notably, mutations to alanine did not alter hormone activity, indicating that only selective substitutions to K or R amino acid residues are causing an enhancement of cAMP and IP 3 production, iodine uptake, proliferation of FRTL-5 cells, thyroxine and progesterone production, respectively ( 1 , 21 , 24 ).…”
Section: Charge Cluster In the Common α-Subunitsupporting
confidence: 57%
“…The effect of these substitutions on the in vitro bioactivity was highly correlated with their effects on the receptor binding activity. It was repeatedly demonstrated in media and buffers with various salt concentrations, and confirmed by studies in other laboratories ( 25 , 26 ) as well as by using CHO-TSHR cells with largely depleted pool of the negatively charged cell surface proteoglycans. Notably, mutations to alanine did not alter hormone activity, indicating that only selective substitutions to K or R amino acid residues are causing an enhancement of cAMP and IP 3 production, iodine uptake, proliferation of FRTL-5 cells, thyroxine and progesterone production, respectively ( 1 , 21 , 24 ).…”
Section: Charge Cluster In the Common α-Subunitsupporting
confidence: 57%
“…Our observations with bursicon reveal another parallel with mammalian heterodimeric cystineknot proteins. Fusion of the a and b subunits of mammalian glycohormones including TSH, LH, and FSH as single soluble peptides also results in ligands that can activate their corresponding mammalian GPCR (Sugahara et al, 1996;Fares et al, 1998;Sen Gupta and Dighe, 2000;Park et al, 2005;Setlur and Dighe, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that single-chain variants of glycoprotein hormones with C terminus of the ␤-subunit fused to the N terminus of the ␣-subunit display bioactivities comparable with those of the corresponding heterodimers (27)(28)(29)(30)(31). However, the relative position of the two subunit does not appear to be important for generation of a biologically active molecule (13).…”
Section: Discussionmentioning
confidence: 99%